Recycling cities for people : the urban design process - Cutler, Laurence Stephan; Cutler, Sherrie Stephens (Boston, Massachusetts : Cahners Books International, Inc., 1976)
New and meaningful juxtaposing of seemingly diverse and unrelated elements has historically been the key capability of the imaginative mind. In this era of specialization and categorization, there is an acute need for this ability and for the person who possesses it-let us call that person a generalist/specialist. The generalist was at one time a singular total individual, the so-called Renaissance man. Now, although great creative capability must still be singular effort, there exists the need for a team approach to problem solving..
I. State of the art: 1. designing for cities -- 2. The state of the environment: a sampler of trends -- 3. Why recycled cities? -- II. Recycling cities: 4. establishing a dialogue -- 5. The process and the prototypes -- 6. The diagnosis -- 7. The treatment -- Glossary for recycling cities -- Selected bibliography -- Illustration credits -- Index.
Includes bibliographical references and index.
Keywords: CITY PLANNING -- UNITED STATES